Characteristics of β-tricalcium phosphate/ZrO2 composite films deposited by pulsed laser deposition at different laser fluences. Issue 23 (1st December 2022) - Wang, J.; Wang, D.G.; Li, X.T.; Zhai, J.Q.; Lu, G.X.; Chen, C.Z.
Abstract: In this paper, the β-tricalcium phosphate (β-TCP)/ZrO2 composite films were prepared at different laser fluences using pulsed laser deposition technology, and the effects of different ablation fluences on the morphology, structure, mechanical properties and in vitro biocompatibility of the films were investigated. The morphology and structure were analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR), the nanohardness and Young's modulus of the films were measured by nanoindentation technique, and the bioactivity of the composite films was studied with simulated body fluid (SBF). The results showed that the increase of ablation fluence increased the number of irregular particles and droplets on the surface of the film, and the intensity of diffraction peaks indicated that the crystallinity level was also improved. The film deposited at 1.02 J/cm 2 exhibited nanohardness and Young's modulus of 5.69 ± 0.28 GPa and 176.33 ± 2.73 GPa higher than the low-fluence film. The high-fluence film rapidly dissolved and re-precipitated in SBF, and the group band of the new phase of re-precipitation was stronger than that of films deposited at 0.57 J/cm 2 and 0.79 J/cm 2 . The research results indicate that the β-TCP/ZrO2 composite film with high crystallinity, good mechanical properties and biocompatibility can be obtained by properly increasing the laser fluence.